Principles of Assessment of Rehabilitation Services in Health Systems: Learning from experiences - Christoph Gutenbrunner; Boya Nugraha (Medical Journals Sweden, 2017)
Objective: Strengthening of health-related rehabilitation services must start from the needs of persons with health conditions experiencing disability and should be implemented within health systems. The implementation of rehabilitation services in health systems should be planned and realized according to the World Health Organization's 6 constituents of health systems (i.e. health service delivery; health workforce; health information systems; essential medicines; financing; and leadership and governance). The development of recommendations based on situation analysis and best-available data is crucial. Methods: In order to facilitate such data collection at a national level, a checklist and a related questionnaire (Rehabilitation Service Assessment Tool (RSAT)) were developed and implemented. The following steps were followed to develop a checklist for implementation of rehabilitation services: a literature search, drafting, checking and testing the list, and development of the RSAT. Results: The RSAT comprises 8 sections derived from 5 main domains of the most important areas of information (i.e. country profile; health system; disability and rehabilitation; national policies, laws, and responsibilities; and relevant non-governmental stakeholders). Conclusion: The implementation of RSAT in different missions has shown that the principles are working well and that RSAT is feasible and helpful. Further field testing is important and the development of an internationally agreed tool should be promoted.